Computational Models of the Auditory System - Meddis, Ray.; Lopez-Poveda, Enrique; Fay, Richard R.; Popper, Arthur N.; SpringerLink (Online service) (New York, NY : Springer US : Imprint: Springer, 2010)
This volume, Computational Models of the Auditory System, has as a systems approach where the focus is on studies which contribute to the big picture of hearing. In effect, the work covered in this volume, and the volume itself, builds a global model of audition. The chapters, rather than focusing on details of individual components of the hearing system, address the concerns of readers and researchers who want to know how the auditory system works as a whole. Contents: Overview - Raymond Meddis and Enrique A. Lopez-Poveda Auditory periphery; from the pinna to the auditory nerve Raymond Meddis and Enrique A. Lopez-Poveda The Cochlear Nucleus - the New Frontier Herbert F. Voigt and Xiaohan Zheng Models of the Superior Olivary Complex Todd R. Jennings and H. Steven Colburn Auditory Cortex: the Final Frontier Jos J. Eggermont Computational Models of Inferior Colliculus Neurons Kevin A. Davis, Kenneth E. Hancock, and Bertrand Delgutte Computational Modeling of Sensorineural Hearing Loss Michael G. Heinz. Physiological Models of Auditory Scene Analysis Guy J. Brown Use of Auditory Models in Developing Coding Strategies for Cochlear Implants Blake S. Wilson, Enrique A. Lopez-Poveda, and Reinhold Schatzer Silicon Models of the Auditory Pathway André van Schaik, Tara Julia Hamilton, and Craig Jin About the Editors: Raymond Meddis is Director of the Hearing Research Laboratory in the Department of Psychology at the University of Essex. Enrique A. Lopez-Poveda is Director of the Auditory Computation and Psychoacoustics Unit of the Neuroscience Institute of Castilla y León, University of Salamanca. Arthur N. Popper is Professor in the Department of Biology and Co-Director of the Center for Comparative and Evolutionary Biology of Hearing at the University of Maryland, College Park. Richard R. Fay is Director of the Parmly Hearing Institute and Professor of Psychology at Loyola University of Chicago. About the series: The Springer Handbook of Auditory Research presents a series of synthetic reviews of fundamental topics dealing with auditory systems. Each volume is independent and authoritative; taken as a set, this series is the definitive resource in the field.
Overview -- Auditory Periphery: From Pinna to Auditory Nerve -- The Cochlear Nucleus: The New Frontier -- Models of the Superior Olivary Complex -- The Auditory Cortex: The Final Frontier -- Computational Models of Inferior Colliculus Neurons -- Computational Modeling of Sensorineural Hearing Loss -- Physiological Models of Auditory Scene Analysis -- Use of Auditory Models in Developing Coding Strategies for Cochlear Implants -- Silicon Models of the Auditory Pathway.
Keywords: Neurosciences; Neurology .; Neurobiology; Neurosciences; Neurology; Neurobiology